Artefatos para fisioterapia aquática: posicionador cervical e prancha para propriocepção e estímulo tátil - Roveda, Patrícia Oliveira (2004)
Water is essential in the life of human beings, and, if used in therapeutic way through the Aquatic Physical Therapy, it promotes health and the recovery of countless diseases. In this work some of the artifacts used in the Aquatic Physical Therapy were analyzed with the objective of proposing their improvement. For that, supports for head and cervical column and boards already available in the Brazilian market, were selected for study. A survey of users' satisfaction it was made, with base in interviews with patients and reports of physiotherapists' experiences. The artifacts were considered in agreement with the stages suggested by design methods. Then recommendations were offered in order to present therapeutic options for those who employ such products with therapeutic ends. The main contribution of this study is to demonstrate to physiotherapists one way in which they cam participate in morphologic, functional and use evaluation of artifacts of their everyday use, and the professional role in the improvement of the function of such products.